Subsistence Strategies and Resource Use Among the Santals of Srirampur in Assam - Saurabh Mardi; Hilloljyoti Singha (Ethnobiology Letters, 2025)
The Santals, one of India's largest Indigenous tribal communities, are primarily found in regions of India, Bangladesh, Nepal, and Bhutan. They share a common language and cultural traditions. The study discusses how the Santals use natural resources including bushmeat, often gathered from the forest or densely vegetated areas in Srirampur, the west border of Assam in North-east India. A structured survey and interviews were carried out among 111 residents. The interviewed community depended significantly on the forest, collecting natural resources such as food, medicinal plants, and non-timber forest products (NTFPs). Hunting was prevalent in the community. Hunters were significantly younger (21.54±8.21 years old) than non-hunters (47.96±10.19 years old) and most preferred catapults to traps. Mass hunting occurred occasionally and was mostly done by children for leisure. Birds were the most targeted animals, while frogs and rodents were also hunted. The primary driver for hunting was consumption and bushmeat was not sold in markets. Other hunting includes species of mollusks and fish. The illiterate members of the tribe were not aware of NGO and state-led conservation efforts although they supported them. This study discusses Santal culture, Santal attitudes toward natural resources, and stresses the need for governmental intervention and awareness programs.